Guided bending experiment for the characterisation of CFRP in VHCF-loading. (September 2016) - Koch, I.; Just, G.; Koschichow, R.; Hanke, U.; Gude, M.
Abstract: The effective experimental characterisation of the damage and failure behaviour of polymer based composites under VHCF-loading depends directly on the development of reliable accelerated fatigue test methods. Here, a guided-bending fatigue experiment in forced excitation is proposed. Key requirements are: high frequency fatigue without significant warming of the specimen, homogeneous stress distribution, widely automated control and in situ crack determination. Using analytical and experimental investigations, a significant improvement of the test stand design, reported earlier [1] has been found in the form of a shaker based bending test stand with kinematically guided displacement. Improvements in the area of durability, homogeneity of the stress state, repeatability of the test and control have been achieved.